Investing in Gender Equality : Looking Ahead - Buvinic, Mayra (World Bank, Washington, DC, 2012)
The financial crisis of 2008-09 has highlighted the need for greater attention to gender, both to address the vulnerability of countries to global shocks and to reach growth and poverty reduction goals. Investments in girls and women need to be scaled up substantially in response to this and other recent crises and, looking ahead, to alleviate demographic stresses and harness demographic opportunities for growth. This is the case because the fate of women and girls, especially in low-income countries and low-income households, is closely linked to the economic prospects of these countries and these households.